Management education for corporate social performance - Stachowicz-Stanusch, Agata; Amann, Wolfgang (Emerald Publishing Limited : Information Age Publishing Inc., 2018)
The book Management Education for Corporate Social Performance is our endeavor to answer the following question: How can the academic world develop and apply a proper concept of corporate social performance to ensure more impact? The authors from different cultures, countries and educational systems present a rich diversity of insights and solutions. The book combines state-of-the-art international views, which can inspire academia as well as corporate practices.
Keywords: Social responsibility of business -- Study and teaching.; Business & Economics -- Business Ethics.; Business ethics and social responsibility.; elektronické knihy; electronic books